Captain Underpants and the wrath of the wicked Wedgie Woman : the fifth epic novel - Pilkey, Dav, 1966- (New York : Blue Sky Press, 2001)
George and Harold create the monstrous Wedgie Woman and Captain Underpants must save the world from her.
School Library Journal, October 2001.
Booklist, January 2002.
Criticas starred, January 2004.
Kirkus Review, July 2001.
4.4
3-6
Keywords: Heroes -- Fiction; Monsters -- Fiction; Schools -- Fiction; School principals -- Fiction; Captain Underpants (Fictitious character) -- Fiction; Humorous stories; Heroes and heroines -- Fiction; Monsters -- Fiction; School stories; School superintendents and principals -- Fiction; Captain Underpants (Fictional character) -- Fiction; Humorous fiction; Humorous stories; Heroes -- Fiction